P0215EXCESSIVE TISSUE SODIUM STORAGE IN PATIENTS WITH NON-DIALYSIS DEPENDENT CARDIO-RENAL SYNDROME IS COMPARABLE TO HEMODIALYSIS PATIENTS. (6th June 2020) - Lemoine, Sandrine; Salerno, Fabio; Akbari, Alireza; McIntyre, Christopher
Abstract: Background and Aims: Both CKD and heart failure (HF) are characterized by a propensity to retain sodium. Renal dysfunction worsens the progression of heart failure and is associated with worse outcomes. This may be a result of synergistic aggravation of sodium retention by the two conditions. We aimed to compare tissue Na storage in skin and muscle between cardiorenal (CR) patients and patients with a range of renal dysfunction, including those requiring hemodialysis (HD). Method: Proton and 23 Na images of the lower limb were acquired on a 3T MRI. We studied 9 CR patients, 7 matched CKD 2-5 patients (without HF) and 31 established HD patients. Regions of interest including skin and soleus were drawn on images to provide a quantitative sodium measurement and these tissue concentrations compared between groups. Blood samples were drawn at each scan in all patients. Spot urine samples were collected for CR patients. Results: For CR patients, mean age was 66 ± 8 years, 78% of male, mean estimated glomerular filtration rate (eGFR) was 52 ± 18 mL/min/1.73m 2, urea was 11 ± 6 mmol/L. For HD patients, mean age was 66 ± 8.7 years, 68% of male and mean dialysis vintage was 38 ± 37 months for HD patients. Mean age was 63 ± 8, 71 % of male, eGFR 45 ± 29 mL/min/1.73m 2 for CKD patients. CR patients displayed an increased amount of salt in skin (32.5 ± 13 mmol/L) and muscle (26 ±4 mmol/L) with levels significantly higher than that seen in GFR matched controls (without HF) and comparable to HD patients (31 ±12 and 28 ± 6 mmol/L p=0.9 and p=0.3 respectively) without meaningful residual renal function. Conclusion: The combination of HF and CKD is associated with intense tissue Na storage; resulting in tissue Na accumulation in CR patients (with reasonably well-preserved renal function) similar to CKD patients requiring HD.